2019
DOI: 10.1016/j.ejro.2019.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Can fully iterative reconstruction technique enable routine abdominal CT at less than 1 mSv?

Abstract: Objective We assessed the effect of the forward projected model-based reconstruction technique (FIRST) on lesion detection of routine abdomen CT at <1 mSv. Materials and methods Thirty-seven adult patients gave written informed consent for acquisition of low-dose CT (LDCT) immediately after their clinically-indicated, standard of care dose (SDCT), routine abdomen CT on a 640-slice MDCT (Aquillion One, Canon Medical System). The LDCT series were reconstructed with FIRST … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…5,6,17 The reason for this discrepancy is probably that our LD-CT protocol did not include iterative reconstruction, which has the potential to lower radiation dose substantially. 18 The low number of patients diagnosed with paralytic ileus in our study is possibly in part due to the high number of CT scans registered as possible intestinal obstruction, where a transition zone was not identified. Additionally, most patients presenting with paralytic ileus at our institution are in the post-operative period.…”
Section: Limitations Of the Studymentioning
confidence: 68%
See 1 more Smart Citation
“…5,6,17 The reason for this discrepancy is probably that our LD-CT protocol did not include iterative reconstruction, which has the potential to lower radiation dose substantially. 18 The low number of patients diagnosed with paralytic ileus in our study is possibly in part due to the high number of CT scans registered as possible intestinal obstruction, where a transition zone was not identified. Additionally, most patients presenting with paralytic ileus at our institution are in the post-operative period.…”
Section: Limitations Of the Studymentioning
confidence: 68%
“…5,6,17 The reason for this discrepancy is probably that our LD-CT protocol did not include iterative reconstruction, which has the potential to lower radiation dose substantially. 18…”
Section: Discussionmentioning
confidence: 99%
“…These differences did not lead to significant differences in subjective image quality, as delineation of vasculature is but one aspect of overall image quality. While Singh et al or Tabari et al [22,28] suggest to link the evaluation of image quality to the clinical task of lesion detection, this approach was not applicable to this study as not all patients had lesions in all three evaluated body regions. In consequence, future studies may evaluate different aspects of image quality to provide a more complete evaluation for different clinical tasks.…”
Section: Discussionmentioning
confidence: 93%
“…There has been limited testing of the use of FIRST algorithms in abdominal imaging so far. Tabari et al showed the possibility of using FIRST reconstruction for sub-Millisievert imaging, showing significant increases in SNR and CNR of abdominal lesions in comparison to FBP in sub-Millisievert CT imaging (27). Our study only evaluated lesions in a standard imaging protocol, without additional analysis of ultra-low-dose imaging.…”
Section: Discussionmentioning
confidence: 99%